2020
DOI: 10.1016/j.cogpsych.2020.101329
|View full text |Cite
|
Sign up to set email alerts
|

Conditionals and testimony

Abstract: Conditionals and conditional reasoning have been a long-standing focus of research across a number of disciplines, ranging from psychology through linguistics to philosophy. But almost no work has concerned itself with the question of how hearing or reading a conditional changes our beliefs. Given that we acquire much-perhaps most-of what we believe through the testimony of others, the simple matter of acquiring conditionals via others' assertion of a conditional seems integral to any full understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…For example, research on conditional reasoning has shown that people’s assumptions about the causal structure (Bonnefond et al, 2014; Byrne, 1989; Byrne et al, 1999; Espino & Byrne, 2020) and their normative expectations about the frequency of events (Oaksford & Chater, 1994, 2003) affect what inferences people draw. Precisely what people infer from conditional statements is still very much under investigation (Barrouillet et al, 2008; Collins et al 2020; Khemlani & Johnson-Laird, 2013; Sebben & Ullrich, 2021; Skovgaard-Olsen et al, 2021). Given the tight relationship between conditionals and causality (e.g., Goldvarg & Johnson-Laird, 2001; Over et al, 2007), we suspect that inferences from conditional statements, just like inferences from explanations, may be illuminated by considering what role these statements play in communication (see also Evans, 2005; Johnson-Laird & Byrne, 2002; Sebben & Ullrich, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, research on conditional reasoning has shown that people’s assumptions about the causal structure (Bonnefond et al, 2014; Byrne, 1989; Byrne et al, 1999; Espino & Byrne, 2020) and their normative expectations about the frequency of events (Oaksford & Chater, 1994, 2003) affect what inferences people draw. Precisely what people infer from conditional statements is still very much under investigation (Barrouillet et al, 2008; Collins et al 2020; Khemlani & Johnson-Laird, 2013; Sebben & Ullrich, 2021; Skovgaard-Olsen et al, 2021). Given the tight relationship between conditionals and causality (e.g., Goldvarg & Johnson-Laird, 2001; Over et al, 2007), we suspect that inferences from conditional statements, just like inferences from explanations, may be illuminated by considering what role these statements play in communication (see also Evans, 2005; Johnson-Laird & Byrne, 2002; Sebben & Ullrich, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Conflict of Interest The authors declare no competing interests. 17 Collins et al (2020) show that no present Bayesian approach accounts satisfactorily for the behavioral data, including a precursor of Eva et al's updating strategy based on distance minimization to be found in Eva and Hartmann (2018). Vandenburgh (2021Vandenburgh ( , p. 2428) puts forth a promising account, where the first step of learning a conditional is to learn a causal model, or a set of structural equations, that expresses "the right dependence" between the conditional's antecedent and consequent.…”
Section: Declarationsmentioning
confidence: 99%
“…(emphasis added, Rogers et al, 2004, p. 229) The use of "may" makes the syllogism probabilistic modus ponens in a clear way, which might not leave the door open to accidentally affirming the consequent. Importantly, however, this is only true in a fully formal setting and natural language can still lead to affirming the consequent Collins, Krzyanowska, Hartmann, Wheeler, & Hahn, 2020). Avoiding affirming the consequent can also be subserved by the clarification that ANNs "may simply rely on brute-force memorization and interpolation to learn how to generate the appropriate linguistic outputs in light of prior contexts" (Goldstein et al, 2021) -something which does appear to be true in certain contexts (Zhang, Bengio, Hardt, Recht, & Vinyals, 2016).…”
Section: Impediments To Inferencementioning
confidence: 99%